Complete Response after Long-Term 2nd Line Treatment with Trabectedin in a Hemodialyzed Patient with Metastatic High-Grade Ovarian Sarcoma, Case Report and Short Review - Konstantinos, Efthymiadis; Christos, Adamidis; Chrysanthi, Koukoutzeli; Vassiliki, Tzelepi; Eleni, Timotheadou (Archives of Clinical and Medical Case Reports, 2019)
Primary ovarian sarcomas are very rare tumours and are characterized by poor prognosis. Surgical treatment is mainly based on epithelial ovarian cancer debulking approaches, while chemotherapy is based on data extrapolation from studies in sarcomas of other primary sites. Trabectedin has been established as a standard of care for the treatment of soft-tissue sarcomas in the 2nd line setting. So far, no data from randomized clinical trials support specific maximum number of cycles of trabectedin for any gynaecological sarcoma. Moreover, limited evidence in the literature supports the feasibility and safety of trabectedin administration in haemodialyzed patients. This report presents the case of a 48-year old female diagnosed with metastatic high-grade undifferentiated sarcoma of the right ovary. She underwent primary surgery followed by 1st line chemotherapy with doxorubicin plus ifosfamide, and had a partial response after cycle 3. However, treatment tolerance was very poor with grade 3 and 4 hematologic and non-hematologic toxicities, including the development of chronic kidney failure that required permanent haemodialysis. Treatment was changed to trabectedin, leading to a complete response that is ongoing and lasts for over 2 years. Our case supports safety of long-term trabectedin administration in a hemodialyzed patient with the achievement of durable complete disease response on the metastatic setting.